(untitled) - Casteel, Joan (Boston, Mass., 2010)
ORACLE 11G: SQL is not simply a study guide; it is written for individuals who have just a basic knowledge of databases and can be utilized in a course on this latest implementation of SQL from Oracle.
Keywords: Oracle (Computer file),SQL (Computer program language),Relational databases,Database management